Linkage study of the D5 dopamine receptor gene (DRD5) in multiplex Icelandic and English schizophrenia pedigrees. - Kalsi, G; Sherrington, R; Mankoo, BS; Brynjolfsson, J; Sigmundsson, T; Curtis, D; Read, T; Murphy, P; Butler, R; Petursson, H; Gurling, HM (1996)
OBJECTIVE: The authors investigated the possibility that genetic variation or mutation of the dopamine D5 receptor gene might modify susceptibility to schizophrenia. METHOD: Twenty-three Icelandic and English pedigrees containing multiple cases of schizophrenia were genotyped by using a highly informative microsatellite for the D5 dopamine receptor gene DRD5. RESULTS: By means of three different affection models, negative lod scores were obtained under assumptions of autosomal dominant and recessive inheritance. There was no evidence for locus heterogeneity. Nonparametric extended relative pair analysis also produced negative results. CONCLUSIONS: These data indicate that mutations of the D5 dopamine receptor gene are not a major cause of schizophrenia in these pedigrees. Because of the probable existence of locus heterogeneity, the D5 receptor gene may be of etiologic importance in other families with schizophrenia.